Issues in Multi-Agent Systems The AgentCities.ES Experience - Moreno, Antonio; Pavón, Juan (Whitestein Series in Software Agent Technologies and Autonomic Computing, 2008)
The agent paradigm has been a subject of research for the last years, and the purpose of this book is to present current status of this technology by looking at its application in different domains, such as electronic markets, e-tourism, ambience intelligence, and complex system analysis. It starts by discussing software engineering issues for the development of multi-agent systems, how much it costs to build a multi-agent system, and which methods and tools are currently available. Next chapters present some of the most relevant aspects that are considered for the development of multi-agent systems: ubiquitous computing, learning and planning, trust and security, electronic institutions and swarm intelligence. Last chapters focus on concrete applications of physical agents and e-tourism applications, to illustrate how to integrate the previously discussed aspects. The book is written by researchers with experience in technology transfer, and therefore it is oriented to practice.